The effect of traditional game Congklak Lidi with BERLIAN method to improve honest attitude to the children - Iswinarti (Universitas Muhammadiyah Malang, 2021)
The Congklak Lidi is a traditional game that has high values in building children’s character. The good values in this game is to build an honest attitude. Among the various traditional games that have been researched, found that the traditional Congklak Lidi has values that could stimulate children’s honesty. The purpose of this study was to determine does the game of Congklak Lidi could increase honesty in children. The research was experimental design with pretest-posttest control group. The research subjects were elementary school students in Dau (a sub-district in Malang). The research instrument used an attitude of honesty scale and was completed with interviews and observations. The data were analyzed by using t-test. The results of the study showed that the game of Congklak Lidi with the BERLIAN method signiﬁcant increase the attitude of honesty in children. The honesty attitude occurs in aspect of cognitive, aspect of conative, and aspect of affective.